Aleppo in Asia: Mercantile networks between Syria, China and post-Soviet Eurasia since 1970. (7th December 2018) - Anderson, Paul
ABSTRACT: Indian Ocean and Mediterranean studies have highlighted the limitations imposed on our understanding of the dynamics of West Asia by the paradigm of area studies and the category of the 'Middle East'. But less attention has been paid to how expansive perspectives that do not invoke an explicitly maritime geography might enrich our understanding of the region's formative connections. This article seeks to locate the modern city of Aleppo in a trans-regional Asian geography by tracing the shifting history of mercantile networks that connected Aleppo to other parts of Eurasia – notably, parts of the formerly Soviet world and the city of Yiwu in Southeast China. It highlights the importance of trans-regional flows of Soviet patronage, and then Chinese state subsidies and credit, in embedding Aleppo into these expansive circuits. It also argues that these flows have fostered the emergence of a hitherto-unstudied business class in Syria.